Morphodiagnostic Anatomy of Coxo-femoral Joint in Dog - Nidhi Gupta; R. Vaish; R. K. Sharma; A. Shahi; A. Mishra; P. Jain; S. Tekam (Indian Journal of Veterinary Anatomy, 2024)
The present study was conducted on twelve (n=12) non-descript dogs irrespective of sex which were divided into two groups viz; group I (3-5 months of age) and group II (1-8 years of age). After radiographic and sonographic evaluation, dissection of hip joints was done via latero-medial approach. Biometric measurement (cm) of ligaments and articular surfaces were recorded. In all the hip joints, an additional strong strand branched off from the ligament of femoral head and traversed in caudal direction through the acetabular notch. The ligament was found to be attached with transverse acetabular ligament when it crossed the latter and its fibres attached on cranioventral surface of the body of the ischium. This ligament was named as accessory ligament as it complemented the ligament of femoral head. Mean length of ligament of femoral head was 1.45 ± 0.02 cm and 1.82 ± 0.03 cm in group I and II, respectively. A band of fibrocartilage, labrum was attached with margin of acetabular rim. The mean values of different measurements of articular surfaces and ligaments were found significantly higher in the dogs of group II. Radiographic observations revealed significantly wider joint space in group I. The contour of acetabulum, femoral head and Ilio-psoas muscles were visualized very well in sonogram, when transducer was placed transversely on lateral surface of hip craniomedial to greater trochanter with medial rotation of femoral head.